GE_GERICHTE C/13844/2007 vom 23. Mai 2014 - GE Cour de justice (2014)
SUCCESSION; EXÉCUTEUR TESTAMENTAIRE; RESPONSABILITÉ DE DROIT PRIVÉ; LIQUIDATION(EN GÉNÉRAL) | CC.517; CO.394; LDS.31.1; LDS.53.1; LDS.53.2; LDS.60.1; LDS.61A; aLPC.176.1; aLPC.181.3